Looking inside an avalanche using a novel radar system. (January 2014) - Keylock, C.J.; Ash, M.; Vriend, N.; Brennan, P.V.; McEwaine, J.N.; Sovilla, B.
<x xml:space="preserve">Abstract</x> Snow avalanches are a significant natural hazard in alpine regions and their flow dynamics have similarities to pyroclastic flows and other geological mass movements. However, the potential for artificial release and the temporary nature of their deposits makes them somewhat easier to study. This article explains recent developments in radar technology for imaging these flows. These new data mean that, for the first time, we are seeing the whole flow averaged over spatial scales that are dynamically relevant. This provides an opportunity to properly test existing models for the dynamics used in risk applications and to gain knowledge of the flow physics, which will guide the next generation of model formulations.